Non-prescription sale and dispensing of antibiotics in community pharmacies in Zambia. Issue 12 (1st December 2016) - Kalungia, Aubrey Chichonyi; Burger, Johanita; Godman, Brian; Costa, Juliana de Oliveira; Simuwelu, Chimwemwe
ABSTRACT: Background : In Zambia, antibiotics are categorized as prescription-only medicines. Antibiotics dispensed without a prescription pose a public health threat, which is a concern. Consequently, the aim is to ascertain the extent of non-prescription sales and dispensing of antibiotics in community pharmacies in Zambia. Methods : The practice of non-prescription sale and dispensing were assessed in 73 randomly selected community retail pharmacies, using a structured interviewer-administered questionnaire with simulated case scenarios. Results : Majority (97%) stated that clients frequently requested non-prescribed antibiotics. Interviewees usually asked clients' indications (94%), counselled on dosing (96%) and suggested changes to antibiotic choices (97%). All (100%) dispensed non-prescribed antibiotics. Commonly dispensed antibiotics included amoxicillin (52%), cotrimoxazole (25%) and metronidazole (23%). Non-prescription sale and dispensing of antibiotics was significantly associated with interviewees' professional qualification in four out of five simulations. Conclusion : Non-prescription sale and dispensing of antibiotics is widespread in Zambia. Concerted public and professional interventions are needed coupled with stronger regulatory enforcement to reduce this.